PENDEFINISIAN KEBUTUHAN FUNGSIONAL SISTEM UNTUK RANCANG BANGUN KNOWLEDGE MANAGEMENT SYSTEM PT. TELKOMSEL REGIONAL SUMBAGSEL - Hairun Nissa; Muhammad Ihsan Jambak (Universitas Sriwijaya, 2016)
Abstract Cellular Telecommunications Operator companies are now increasingly compete in creating new innovations for improving competitive advantage. Competition is changing the paradigm of the resource base of competitiveness into a knowledge base of competitiveness. Companies are increasingly aware of the importance of knowledge as a means to win the competition. The organizational knowledge comes from the knowledge possessed by the employees, therefore the company needs to foster a culture of knowledge sharing. This situation has created the need for PT. Telkomsel Regional Sumbagsel to manage its knowledge assets. This effort can be achieved using Knowledge Management strategy. This study aims to find the features needed to build Knowledge Management Systems in order to foster a culture of knowledge sharing in the company. Researchers test the features required to grow the user behavior of knowledge sharing based on the Theory of Planned Behavior. It is predicted with high accuracy of attitude toward knowledge sharing behavior, subjective norms, and behavior control. Development of this system using the Framework for the Application of Systems Thinking (FAST). This system is tested and able to facilitate knowledge sharing among employees in order to improve learning skills and learning capability. Keywords: Knowledge Management , Knowledge Management System, Knowledge Sharing, Theory of Planned Behavior Â Abstrak Perusahaan Operator Telekomunikasi Seluler sekarang ini semakin bersaing dalam menciptakan inovasi baru demi meningkatkan keunggulan kompetitif. Persaingan ini mengubah paradigma dari resource base competitiveness menjadi knowledge base competitiveness. Perusahaan semakin menyadari pentingnya pengetahuan sebagai sarana untuk memenangkan persaingan. Pengetahuan organisasi berasal dari pengetahuan yang dimiliki oleh karyawan untuk itu perusahaan perlu menumbuhkan budaya knowledge sharing. Kondisi ini telah menciptakan kebutuhan bagi PT. Telkomsel Regional Sumbagsel untuk mengelola aset pengetahuan yang dimilikinya. Upaya ini dapat dicapai dengan menggunakan strategi Knowledge Management. Penelitian ini bertujuan untuk menemukan fitur-fitur yang diperlukan dalam membangun Knowledge Management Systems sehingga dapat menumbuhkan budaya knowledge sharing pada perusahaan. Peneliti menguji fitur-fitur yang diperlukan user untuk menumbuhkan perilaku knowledge sharing berdasarkan Theory of Planned Behavior. Hal ini diprediksi dengan akurasi yang tinggi dari sikap terhadap perilaku knowledge sharing, norma subyektif, dan kontrol perilaku. Pembangunan sistem ini menggunakan metode Framework for the Application of System Thinking (FAST). Sistem ini telah diujikan dan mampu memfasilitasi kegiatan knowledge sharing antar pegawai sehingga dapat meningkatkan learning skill dan learning capability. Kata kunci: Knowledge Management , Knowledge Management System, Knowledge Sharing, Theory of Planned Behavior